ANALISIS KEUNGGULAN KOMPARATIF DAN FAKTOR YANG MEMPENGARUHI KINERJA KOPERASI DI PULAU JAWA - Adrian Tri Sasongko; Yeti Lis Purnamadewi; Sri Mulatsih (JURNAL EKONOMI DAN KEBIJAKAN PEMBANGUNAN, 2017)
Development of cooperatives is an important element that must be done in order to realize the national economic development because the cooperative able to accommodate the community in achieving the goal of improving the welfare of the people based on the principle of mutual cooperation. Differences in regional characteristics lead to diversity in the development and development of cooperatives. Java Island with rapid economic growth, able to build cooperatives in large numbers but the performance of cooperatives and growth is still fluctuating. Therefore, this study aims to determine the comparative advantage in cooperative development and analyze the factors that affect the performance of cooperatives in Java. This research uses secondary data with Method of Econometrika Data Panel and Method of Economic Performance Index of Regional Cooperation (PEKR Index). The results showed that the provinces of Central Java and Yogyakarta have a comparative advantage in the economic development of cooperatives in 2011-2015. Factors affecting the performance of the cooperative is the number of active cooperatives, the number of cooperative employees, own capital cooperatives and PDRB. Keywords: Comparative advantage, Cooperative, Performance, Panel data